Regioselectivity Issues in the Addition of Grignard Reagents to Trifluoromethylated α‐Bromoenones. Issue 11 (7th March 2019) - Romanov, Alexey R.; Cahard, Dominique; Rulev, Alexander Yu.
Abstract : The regioselectivity of addition of organomagnesium reagents to trifluoromethylated α‐bromoenones is reported. Alkyl and aryl Grignard reagents undergo 1, 4‐ and/or 1, 2‐addition but, in contrast to non‐fluorinated α‐bromoenones, the former direction is dominant for these fluorinated analogs. The high 1, 4‐regioselectivity observed in most cases reflects the influence of the trifluoromethyl group on the direction of nucleophilic attack. Abstract : In contrast to non‐fluorinated α‐bromoenones their fluorinated analogs react with alkyl and arylmagnesium bromides leading to saturated CF3 ‐ketones as major reaction adducts. The regioselectivity of addition depends strongly on the nature of the Grignard reagent.